W warmińskiej chacie i zagrodzie przełomu XIX i XX wieku – życie codzienne w świetle zbiorów Muzeum Warmińskiego Gospodarstwa (Muzyjum Warnijskygo Gburstwa) w Giławach - Lewandowska, Izabela (W zwierciadle rzeczy, 2022)
The article presents the everyday life of the Warmian population in the second half of the 19th century on the basis of the collections gathered in an original cottage in the village of Giławy. The cottage was built in 1880 in a village colony surrounded by forests and fields. In 2013, it houses the Museum of the Warmian Farm. The owners not only live in this house, but also search for its history. They collect souvenirs related to the home and everyday life of the rural population of Warmia. We can see there not only antique furniture in original interiors, but also the layout of the house integrated into the Warmian landscape. The article discusses a Warmia farmstead and a cottage as examples of traditional rural construction, as well as ethnographic collections – furnishings of residential rooms, kitchens, hallways and basements. The multitude of ethnographic material collected in the Museum allows you to get to know and imagine the former life of the inhabitants as if in a mirror.